2022
DOI: 10.4155/fmc-2022-0139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Modeling Studies of 1-Benzyl-2-Indolinones As Selective AChE Inhibitors

Abstract: Background: Possible bioisosteres can be developed by replacing the 1-indanone ring (one of three pharmacophore groups) of donepezil with an indoline ring. As H2S donors, thioamide, thiocarbamate and thiourea groups are also critically important. Materials & methods: The 1-benzyl-2-indolinones 6a–n were designed using molecular modeling and synthesized, and their acetylcholinesterase and butyrylcholinesterase inhibitory effects were then investigated. Results: The compounds 6h (inhibition constant [ Ki] = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In vitro evaluations exhibited significant inhibition of derivatives, in which the most potent analog exhibited more than 2-fold potency compared with donepezil. 64 The structure-activity relationship (SAR) also demonstrated that substitution at the different positions of the indolidinone ring significantly affects the potency.…”
Section: Designmentioning
confidence: 99%
“…In vitro evaluations exhibited significant inhibition of derivatives, in which the most potent analog exhibited more than 2-fold potency compared with donepezil. 64 The structure-activity relationship (SAR) also demonstrated that substitution at the different positions of the indolidinone ring significantly affects the potency.…”
Section: Designmentioning
confidence: 99%